Manifesta young women, feminism, and the future - Baumgardner, Jennifer (1970- ).; Richards, Amy (Farrar, Straus and Giroux, 2000)
In the year 2000, girl culture was clearly ascendant. From Lilith Fair to Buffy the Vampire Slayer to the WNBA, it seemed that female pride was the order of the day. Yet feminism was also at a crossroads; "girl power" feminists were obsessed with personal empowerment at the expense of politics, while political institutions such as Ms. and NOW had lost their ability to speak to a new generation. In Manifesta, Jennifer Baumgardner and Amy Richards brilliantly revealed the snags in each feminist hub, all the while proving that these snags had not imperiled the future of the feminist cause. The book went on to inspire a new generation of female readers, and has become a classic of contemporary feminist literature.
Keywords: 1900-1999; 1990-1999; amériques; cours; cycles supérieurs; fem1000; fem9000; militance; mouvements féministes; premier cycle; périodes historiques; régions géographiques; thématiques; états-unis; études culturelles

Mort ou fif: la face cachée du suicide chez les garçons - Dorais, Michel; Lajeunesse, Simon Louis (VLB éditeur, 2000)
A partir de témoignages et récits de vie, cet ouvrage met en lumière la relation entre le mépris et l'ostracisme dont sont victimes les adolescents homosexuels ou considérés comme tels et leur haut taux de suicide. Une version revue et corrigée d'un document publié par le Centre de recherche sur les services communautaires de l'Université Laval (octobre 2000).
Section: 110 pages ; 23 cm
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; hétérosexisme; identités LGBTQIA2+; premier cycle; périodes historiques; queer; québec; régions géographiques; santé; shm4000; systèmes d'oppressions; thématiques

Controversy and coalition: The new feminist movement across three decades of change - Ferree, Myra Marx; Hess, Beth B. (Routledge, 2000)
Controversy and Coalition is a comprehensive and engaging overview of the American women's movement from the 1960's to the 1990's.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amériques; histoire des femmes*; histoire et politique; militance; mouvements féministes; périodes historiques; ressource en ligne; régions géographiques; thématiques; états-unis

Genders - Glover, David; Kaplan, Cora (Routledge, 2000)
"Gender" has, in recent years, become one of the busiest terms in literary and cultural theory, as well as being one of the most contested. David Glover and Cora Kaplan chart the main lines of contemporary debate surrounding gender in a guide which:* presents a history of the term, from the sexology of psychoanalysis of the 1960s to its current usage within the interdisciplinary field of gender studies* looks at the major perspectives on gender from second-wave feminist writers and critics* examines new work on masculinity in literary and cultural studies* assesses how the creation of new queer and gendered identities has impacted the study of literature* surveys empirical and theoretical work on readership and spectatorship, looking in detail at modes of fantasy, cultural consumption, reader response and fan cultures.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; amériques; antiféminisme; approches et analyses; cours; culture populaire; discipline; fem1000; littérature; masculinisme; premier cycle; périodes historiques; queer; ressource en ligne; régions géographiques; états-unis; études culturelles; études littéraires

La construction de savoirs d'expérience chez des intervenantes d'organismes communautaires pour femmes sans-abri : un processus participatif, collectif et non planifié - Racine, Guylaine (Nouvelles pratiques sociales, 2000)
Cet article présente les résultats d'une étude portant sur la description du processus d'apprentissage expérientiel d'intervenantes oeuvrant dans des organismes communautaires pour femmes sans-abri. L'analyse des données révèle que les savoirs d'expérience de ces intervenantes se construisent progressivement, à travers un processus de réflexion sur l'action suscité par des situations problématiques qui surgissent de la pratique. L'analyse met également en relief le rôle central du collectif d'intervenantes dans la construction de ces savoirs. Ces résultats permettent de revitaliser le concept d'apprentissage expérientiel : plutôt qu'un processus individuel de production de savoirs, il est possible de l'envisager sous l'angle d'une co-construction de savoirs à laquelle participent des actrices concernées par un même objet.
Keywords: 1900-1999; 1990-1999; amériques; discipline; intervention sociale; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; travail social

Has feminism changed science? - Schiebinger, Londa (Signs, 2000)
Discusses whether the presence of feminism in science has changed science, discounting the idea that simply encouraging more women to enter science will necessarily produce change and stressing the need for governmental funding and initiatives on women and gender in science. Argues for multiple arenas for change (research priorities, domestic relations, university structures, classroom practices, and home-work relationships.)
Keywords: 1900-1999; 1980-1989; 1990-1999; amériques; histoire et politique; projet charge mentale; pédagogie; périodes historiques; recherches féministes; régions géographiques; thématiques; travail; états-unis